2015
DOI: 10.4236/jss.2015.312008
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents Perception on Environmental Change and Health Risk in Two Divisions of Bangladesh

Abstract: Bangladesh is facing and will have to face all the direct and indirect impacts of environmental change because of its geographical position. It is one of the developing countries susceptible to environmental disaster where almost each and every year environmental change is affecting the human health in a multi-dimensional way. The linkages between health and environmental change are mediated by the complex interactions of population, society and environmental systems. The objective of this study was to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
(19 reference statements)
4
3
0
Order By: Relevance
“…The same result was stated in a research in Bangladesh, where adolescents had a good understanding of the impact of environmental change on health [26]. However, in this research, it was identified that adolescents did not understand deeply what kind of health was affected by climate change.…”
Section: Discussionsupporting
confidence: 71%
“…The same result was stated in a research in Bangladesh, where adolescents had a good understanding of the impact of environmental change on health [26]. However, in this research, it was identified that adolescents did not understand deeply what kind of health was affected by climate change.…”
Section: Discussionsupporting
confidence: 71%
“…People's knowledge level and behavior in Dhaka towards air pollution were low among different age groups, income groups, and occupation groups [63]. Similar findings were found in another study [64]. The overall situation explains many causes of the illiteracy of dwellers to environmental pollution in the study area.…”
Section: Discussion and Policy Implicationssupporting
confidence: 79%
“…Although our participants did not deeply understand CC, they knew that it poses a serious risk to human health and can reduce the quality of life for future generations. The same result was stated in research from Indonesia (Sulistyawati et al 2018) and Bangladesh (Dana et al 2015), where adolescents adequately understood the health impact of environmental change.…”
Section: Discussionsupporting
confidence: 68%